Analisis Muatan Moderasi Beragama Dalam Buku PAI Kelas XII SMA Karya Husni Thoyar Dalam Meningkatkan Sikap Moderat - Rizal, Moh.; Hasan, Mohammad (Kartika: Jurnal Studi Keislaman, 2025)
The phenomenon of radicalism and extremism that occurs in the school environment is an important concern to be resolved immediately in order to achieve the expected climate, namely through Islamic Religious Education learning with a religious moderation perspective. So the purpose of this study is to find out whether there is learning about religious moderation in the Islamic Religious Education book by Husni Thoyar. The method used in this study is library research with the primary source of the Islamic Religious Education book by Husni Thoyar, while the secondary data source is other literature that supports the main source in this study. The data collection in this study is through a review of Islamic Religious Education books and looking for references that are in accordance with the topic being studied, the analysis process is carried out in several ways including reviewing primary books, describing data and discussing it. The results of this study are: 1) the material in the Islamic Religious Education book by Husni Thoyar has 12 chapters including material on verses of the Qur'an, faith, Islamic law, history and morals, 2) material containing the value of religious moderation, namely: 1) material on verses of the Qur'an about tolerance, 2) material on commendable behavior and material on unity and harmony.